2003
DOI: 10.2343/geochemj.37.35
|View full text |Cite
|
Sign up to set email alerts
|

U-Pb zircon ages for a collision-related K-rich complex at Shidao in the Sulu ultrahigh pressure terrane, China.

Abstract: The Shidao complex at the eastern extremity of the Sulu ultrahigh pressure (UHP) terrane is composed of oldest pyroxene syenite, quartz syenite and youngest granite intrusives of the K-rich shoshonitic series. U-Pb zircon dating yields nearly concordant ages of 225 ± 2, 211 ± 3 and 205 ± 5 Ma for pyroxene syenite, quartz syenite and granite, respectively. The ages closely postdate the 240 to 220 Ma UHP metamorphism and correspond to the rapid cooling and exhumation of UHP rocks. A close genetic relation may ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(74 citation statements)
references
References 43 publications
2
69
0
3
Order By: Relevance
“…In addition, the tectonic amalgamation of the Yangtze Plate with the North China Craton is spatially well coupled with the division of lithospheric mantle region of the North China Craton (Figure 8). Magmatism on the eastern and southern margins of the North China Craton in Late Triassic is a representation of cratonic destruction on the margins, no matter they were products in post-collisional extension background or melting of the lithosphere mantle induced by asthenospheric upwelling through the slab window formed by slab breakoff of the deep subducted plate [63,64].…”
Section: Geodynamic Factors Of the Cratonic Destructionmentioning
confidence: 99%
“…In addition, the tectonic amalgamation of the Yangtze Plate with the North China Craton is spatially well coupled with the division of lithospheric mantle region of the North China Craton (Figure 8). Magmatism on the eastern and southern margins of the North China Craton in Late Triassic is a representation of cratonic destruction on the margins, no matter they were products in post-collisional extension background or melting of the lithosphere mantle induced by asthenospheric upwelling through the slab window formed by slab breakoff of the deep subducted plate [63,64].…”
Section: Geodynamic Factors Of the Cratonic Destructionmentioning
confidence: 99%
“…In this respect, the carbonate-and rutile-rich melt metasomatism beneath the Sulu orogen was unlikely to have been simultaneous to continental subduction. Alternatively, seismic investigations on the DabieSulu belt and U -Pb dating results of collision-related K-rich complex from the Sulu orogen suggested that slab breakoff occurred after the Triassic collision (Xu et al, 1999;Chen et al, 2003), which could be a likely mechanism for the metasomatic event. Following slab breakoff, asthenospheric upwelling and lithospheric extension caused the rapid exhumation of the UHP terranes (e.g., Li et al, 1999) and would provide heat supply to melt the trapped subducted continental crust.…”
Section: Conditions For Carbonate-and Rutile-rich Metasomatism Beneatmentioning
confidence: 99%
“…There are also the same episode of alkali granites in the Dabie-Sulu orogenic belt [56,57], which also show the similar patterns of arc-like REE and trace element distribution [5,[58][59][60]. The Neoproterozoic age of inherited zircons in the CB granite indicates that its source is a product of mid-Neoproterozoic rift magmatism along the northern margin of the South China Block.…”
Section: Geodynamic Implicationsmentioning
confidence: 98%